Memperkuat Kapasitas Petani melalui Elektrifikasi Pertanian - Setyawanto, Agus; Hariyadi, Bachtiar; Astutiek, Dwi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The program was conducted over a six-month period (Junet–November 2025) using a participatory approach involving 30 members of local farmer groups. The implementation stages included an initial survey, program socialization, electricity-based technology training, field mentoring, and monitoring and evaluation. The results demonstrated a significant increase in farmers’ knowledge, with an average improvement of 63%, as indicated by an increase in pre-test scores from 50 to 82 in the post-test. Approximately 90% of farmers expressed readiness to adopt the technology, and 27 out of 30 participants were able to operate the electrical equipment independently. From a technical perspective, the use of electric pumps and automated irrigation systems reduced irrigation operational costs by up to 30% and increased rice productivity from 4.8 tons/ha to 5.7 tons/ha. The program also strengthened household food security and improved energy use efficiency. The success of the program was supported by collaboration between PLN as the provider of technical support and Yatim Mandiri Foundation as the social facilitation partner.